Dominant negative suppression of arabidopsis photoresponses by mutant phytochrome A sequences identifies spatially discrete regulatory domains in the photoreceptor. - Boylan, M (1994)
We used the exaggerated short hypocotyl phenotype induced by oat phytochrome A overexpression in transgenic Arabidopsis to monitor the biological activity of mutant phytochrome A derivatives. Three different mutations, which were generated by removing 52 amino acids from the N terminus (delta N52), the entire C-terminal domain (delta C617), or amino acids 617-686 (delta 617-686) of the oat molecule, each caused striking dominant negative interference with the ability of endogenous Arabidopsis phytochrome A to inhibit hypocotyl growth in continuous far-red light ("far-red high irradiance response" conditions). By contrast, in continuous white or red light, delta N52 was as active as the unmutagenized oat phytochrome A protein in suppressing hypocotyl elongation, while delta C617 and delta 617-686 continued to exhibit dominant negative behavior under these conditions. These data suggest that at least three spatially discrete molecular domains coordinate the photoregulatory activities of phytochrome A in Arabidopsis seedlings. The first is the chromophore-bearing N-terminal domain between residues 53 and 616 that is apparently sufficient for the light-induced initiation but not the completion of productive interactions with transduction chain components. The second is the C-terminal domain between residues 617 and 1129 that is apparently necessary for completion of productive interactions under all irradiation conditions. The third is the N-terminal 52 amino acids that are apparently necessary for completion of productive interactions only under far-red high irradiance conditions and are completely dispensable under white and red light regimes.